(untitled) (Research, Society and Development, 2020)
Childhood sexual violence is a complex issue and registered in several countries, being one of the least reported crimes in the world. It is considered as one of the most serious public health problems faced by society, being frequently accompanied by psychological violence, in the form of threats and physical violence directed at the victim or someone she likes. It is important to know how much sexual violence against children occurs in Brazil, mainly because sexual victimization in childhood can have important and lasting psychological effects in the short and long term. This study aims to analyze the occurrence of child sexual violence in 940 university students from Ceará, drawing a profile of the types of violence, characterizing the victim and the aggressor through the application of a self-administered questionnaire. The survey showed that 53% (N = 487) of the students suffered some type of sexual violence in childhood, that is, child sexual abuse and / or sexual violence between peers.